ANALISIS MAKNA PUASA ATAS KECERDASAN EMOSIONAL DI PONDOK PESANTREN LANGITAN WIDANG TUBAN JAWA TIMUR - Muhammad Hasyim (JP : JURNAL PENDIDIKAN, 2017)
This article deals with the meaning analysis of fasting over the emotional intelligence performed by students of Islamic boarding school. In addition to be a form of worship that connect directly between people (who fast) with Allah SWT, fasting has various benefits which impact to social life, those are the positive impact o the five aspects of emotion intelligence offered Goleman namely; self-awareness, self-regulation, moti-vation, empathy and social skills. Form these five aspect, those who often and able to perform maghḍah solemnly and right according to shari’a provision, are capable of possessing the core of human nature in fact. When people an pasting they deserved two glories, those are; glorious in God’s eyes for having a worship worshiped to them, and noble in front of man because of the revealing strong emotional sense to give goodness for the whole of nature in life.Keywords: fasting, Emotional and character